2020
DOI: 10.1088/1742-6596/1569/3/032064
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Antibiotic Use and Germ Map in Pneumonia Patients in Pulmonary Space (Case Study at RSUD dr. Iskak. Tulungagung)

Abstract: Pneumonia is an infection of lung tissue caused by bacteria, fungi, viruses or parasites. Antibiotics is a major therapy in pneumonia. The aim of this study was to determine the amount of antibiotic use in DDD / 100 patient-days and to know the profile of germs map in pneumonia patients in Pulmonary Room Dr. Iskak Hospital, Tulungagung during January-June 2017.The design of this research is observational research method with retrospective data retrieval from patient medical record data and antibiotic usage dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Compared to 98 studies conducted in hospitals in Germany that showed total antibiotic use in sepsis and pneumonia patients of 51.0 DDD/100 patient-days (Scholze et al, 2015) Parenteral Levofloxacin is the most widely used antibiotic in RSUA Surabaya. Similarly, it was found in studies conducted at Dr Iskak Tulungagung Hospital and Dr Moewardi Surakarta Hospital, with the number of Levofloxacin used for consecutive indications of pneumonia reaching 40.14 DDD/100 patient-days and 53.88 DDD/100 patient-days (Ilmi et al, 2020;Muhammad & Mutmainah, 2018). Levofloxacin is among the most widely prescribed types of antibiotics for pneumonia therapy because it is a respiratory fluoroquinolone-class antibiotic that is effective overcoming upper and lower airway infections with high activity against gram-positive bacteria and atypical bacteria cause pneumonia (Daniel H & Lisa G, 2015;Izadi et al, 2019).…”
Section: Discussionmentioning
confidence: 57%
“…Compared to 98 studies conducted in hospitals in Germany that showed total antibiotic use in sepsis and pneumonia patients of 51.0 DDD/100 patient-days (Scholze et al, 2015) Parenteral Levofloxacin is the most widely used antibiotic in RSUA Surabaya. Similarly, it was found in studies conducted at Dr Iskak Tulungagung Hospital and Dr Moewardi Surakarta Hospital, with the number of Levofloxacin used for consecutive indications of pneumonia reaching 40.14 DDD/100 patient-days and 53.88 DDD/100 patient-days (Ilmi et al, 2020;Muhammad & Mutmainah, 2018). Levofloxacin is among the most widely prescribed types of antibiotics for pneumonia therapy because it is a respiratory fluoroquinolone-class antibiotic that is effective overcoming upper and lower airway infections with high activity against gram-positive bacteria and atypical bacteria cause pneumonia (Daniel H & Lisa G, 2015;Izadi et al, 2019).…”
Section: Discussionmentioning
confidence: 57%
“…When evaluating the use of antibiotics before and after intervention, for example, Guidelines for Antibiotic Use (PPAB) (Karuniawati et al, 2021), Antimicrobial Resistance Control Program (PPRA) (Kartika et al, 2019), and Clinical Pathway (Adiwisastra et al, 2019). (Evano Putra et al, 2021) and (Ilmi et al, 2020) selected pneumonia patients in the lung room at the RSUD dr. Iskak Tulungagung for their case studies on the use of antibiotics during the Covid-19 pandemic at the Diponegoro National Hospital. The duration of the investigation period for the selected articles ranged from one month to five years.…”
Section: Resultsmentioning
confidence: 99%